2021
DOI: 10.3892/etm.2021.9898
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR‑145 as a regulator of the cardiomyocyte inflammatory response and oxidative stress under hyperglycemia

Abstract: The current study aimed to explore the effects of microRNA (miR)-145 on the inflammatory response and oxidative stress (OS) in high glucose (HG)-induced cardiomyocytes, as well as the specific mechanism underlying this action. H9c2 cells were treated with 33 mmol/l glucose (HG group) or cotreated with 24.5 mmol/l mannitol and 5.5 mmol/l glucose (hypertonic group), and the expression levels of miR-145 and ADP ribosylation factor 6 (ARF6) were detected. The cells were transfected with pcDNA3.1-ARF6, miR-145 mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…We selected 12 miRNAs associated with diabetic HF. The initial selection of miRNAs in our panel were miR-1 [ 28 , 29 ], miR-21 [ 30 ], miR-29a [ 31 ], miR-30d [ 32 , 33 ], miR-34a [ 34 ], miR-126a [ 35 ], miR-143 [ 36 ], miR-145 [ 37 ], miR-195 [ 38 ], miR-206 [ 39 ], miR-320 [ 39 ] and miR-378 [ 40 ]. We found that the expression of all miRNAs was significantly lower in HFpEF diabetic hearts than in controls ( Figure 5 A–L).…”
Section: Resultsmentioning
confidence: 99%
“…We selected 12 miRNAs associated with diabetic HF. The initial selection of miRNAs in our panel were miR-1 [ 28 , 29 ], miR-21 [ 30 ], miR-29a [ 31 ], miR-30d [ 32 , 33 ], miR-34a [ 34 ], miR-126a [ 35 ], miR-143 [ 36 ], miR-145 [ 37 ], miR-195 [ 38 ], miR-206 [ 39 ], miR-320 [ 39 ] and miR-378 [ 40 ]. We found that the expression of all miRNAs was significantly lower in HFpEF diabetic hearts than in controls ( Figure 5 A–L).…”
Section: Resultsmentioning
confidence: 99%
“…For example, inhibition of miR-155-5p could reduce the level of IL-6 in heart valves and serum in RHD patients and reduce valve inflammation and fibrosis induced by RHD. [ 21 , 22 ] Previous studies have demonstrated the antioxidant and anti-inflammatory effects of miR-145, [ 23 ] such as the downregulation of miR-145-5p expression in left and right atrial appendages in patients with rheumatic mitral valve disease. [ 8 ] A correlation between miR-145 and IL-6 was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between the expression level of miR-222, the estrogen receptor and GLUT4 has also been demonstrated [265]. microRNAs which expression can be regulated by androgens (miR-124 and miR-145) and estrogens (miR-30c) are implicated in thermogenesis regulation by targeting MCT1, LDH and RIP140, respectively [266][267][268]. MCT1 expression is also modulated by miR-342-3p [269].…”
Section: Micrornas Expressed In Adipose Tissue Are Involved In Molecular Mechanism Of Metabolic Diseasesmentioning
confidence: 91%